Tree Growth Yield and Fruit Quality of Different Apple Cultivars Trained as Super Spindle - Emine Kucuker; Kenan Yildiz; Yakup Ozkan (Aceh International Journal of Science and Technology, 2015)
This study was carried out on Topaz, Cooper 39 and Muscat apple cultivars grafted on M27 rootstocks under Tokat ecological conditions during 2008 - 2010. The trees planted in 2.0 m x 0.5 m row spacing (10,000 trees ha-1) and trained to super spindle (SS) training system. The vegetative development, yield and fruit quality performances of the trees supported by wire – pole combination were observed for three years. At the end of the experiment, it was determined that Cooper 39 had a higher trunk cross sectional area (TCA) than Topaz and Muscat. While cumulative yield (CY) per tree and cumulative yield efficiency (CYE) were determined to be the highest in Cooper 39, these values were found to be the lowest in Topaz. CY per hectare over the first three crop year was found to be the highest in Cooper 39 and the yield reached to 142.9 t.ha1. The lowest CY per hectare (69.6 ton ha-1) was determined in Topaz